2016
DOI: 10.1099/jmm.0.000256
|View full text |Cite
|
Sign up to set email alerts
|

Expression of prostaglandin receptors in Chlamydia trachomatis-infected recurrent spontaneous aborters

Abstract: A study was undertaken to quantify the expression of prostaglandin (PG) receptors and find the effect of gestational age on expression of PG receptor genes in Chlamydia trachomatis-infected recurrent spontaneous aborters (RSA). Endometrial curettage tissue (ECT) was collected from 130 RSA (Group I) and 100 age-matched controls (Group II) at the Department of Obstetrics and Gynecology, Safdarjung Hospital, New Delhi (India). PCR was performed for diagnosis of C. trachomatis cryptic plasmid; mRNA expression of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…They found that these women had significantly increased estrogen and decreased progesterone levels compared to uninfected RSA and non-RSA control groups [12]. This study also demonstrated that Chlamydia-infected RSA had increased expression of contractile prostaglandin receptors, which are regulated by hormone concentrations during pregnancy and are involved in initiation of labor [12]. While there could be other reasons for these observations, these data suggest that Chlamydia directly or indirectly cause a shift in estrogen and progesterone levels that can result in spontaneous abortion.…”
Section: Influence Of Natural and Synthetic Fsh On Chlamydia Infectiomentioning
confidence: 98%
See 1 more Smart Citation
“…They found that these women had significantly increased estrogen and decreased progesterone levels compared to uninfected RSA and non-RSA control groups [12]. This study also demonstrated that Chlamydia-infected RSA had increased expression of contractile prostaglandin receptors, which are regulated by hormone concentrations during pregnancy and are involved in initiation of labor [12]. While there could be other reasons for these observations, these data suggest that Chlamydia directly or indirectly cause a shift in estrogen and progesterone levels that can result in spontaneous abortion.…”
Section: Influence Of Natural and Synthetic Fsh On Chlamydia Infectiomentioning
confidence: 98%
“…There are multiple reasons that women experience spontaneous abortion, including an improper balance of hormones during pregnancy [11]. Decreased progesterone levels early during pregnancy can result in spontaneous abortion [12]. A prospective study measured estrogen and progesterone levels in Chlamydia-infected recurrent spontaneous aborters (RSA) during their first trimester.…”
Section: Influence Of Natural and Synthetic Fsh On Chlamydia Infectiomentioning
confidence: 99%